2017
DOI: 10.7150/ijms.21773
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of high-mobility group box protein 1 genetic polymorphisms in rheumatoid arthritis disease outcome

Abstract: Rheumatoid arthritis (RA) is a systemic inflammatory disease that causes chronic inflammation of the joints. Analysis of genetic variants offers promise for guiding treatment and improving outcomes in RA. High-mobility group box protein 1 (HMGB1) is a ubiquitous nuclear protein found in all mammal eukaryotic cells that participates in several biological functions including immune response, cell survival and apoptosis. We investigated the effects of HMGB1 gene polymorphisms on the risk of RA disease progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…It is well recognized that susceptibility for RA disease is influenced by genetic and environmental factors [ 22 , 23 ]. The recent development of biological-based antirheumatic therapies that target inflammatory pathways in RA has enabled increasing numbers of patients to achieve very low levels of disease activity, yet a substantial proportion of RA patients remain treatment-refractory [ 3 , 24 ]. This issue underlines the importance of continuing to investigate the pathogenesis of RA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well recognized that susceptibility for RA disease is influenced by genetic and environmental factors [ 22 , 23 ]. The recent development of biological-based antirheumatic therapies that target inflammatory pathways in RA has enabled increasing numbers of patients to achieve very low levels of disease activity, yet a substantial proportion of RA patients remain treatment-refractory [ 3 , 24 ]. This issue underlines the importance of continuing to investigate the pathogenesis of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is an autoimmune disease characterized by marked hypertrophy and hypervascularity of the synovial tissues and joint destruction, affecting around 1% of the global population [ 1 , 2 ]. Despite the emergence of promising novel therapies in recent years that have enabled a substantial amount of RA patients to achieve disease remission with minimal or no symptoms, a substantial proportion of patients remain treatment-refractory and experience progressive joint and functional destruction or even premature mortality [ 3 , 4 ]. The mortality rates among the RA patients are 1.5 ~ 1.6 times higher than those among the general population [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rheumatoid arthritis (RA) is an autoimmune disease that manifests hypertrophy and hypervascularity in synovial tissues and leads to joint destruction, affecting approximately 1% of the global population [1][2][3][4]. Despite several treatment regimens emerging in recent years that have enabled a substantial portion of RA patients to achieve disease remission with minimal symptoms, some patients remain treatment-refractory and continue to experience progressive joint deterioration and increasing functional limitations, or even premature mortality [5][6][7]. When compared with the general population, RA patients face higher risks of major morbidities, including infection and pulmonary and renal disease, and an approximate 1.5-fold higher risk of mortality [8].…”
Section: Introductionmentioning
confidence: 99%
“…HMGB1 is usually localized in the cell nucleus and is secreted into the extracellular environment in response to different stimuli; either passively during cellular apoptosis or necrosis, or actively following inflammatory signals from activated immune cells or neuronal cells 9 . It has been reported HMGB1 SNPs controls with rheumatoid arthritis disease outcome 10 . Previous research has confirmed the association of HMGB1 SNPs with the susceptibility and progression of disease, such as hepatocellular carcinoma 11 , lung cancer 12 and uterine cervical neoplasia 13 .…”
Section: Introductionmentioning
confidence: 99%